Numerical Simulation of CAARC Standard High-Rise Building Model Based on MRT-LBM Large Eddy Simulation - Rui Zhao; Zehua Feng; Danhui Dan; Yuhang Wu; Xianduo Li (Shock and Vibration)
The calculation of wind load of high-rise buildings depends on the wind pressure distribution data and wind pressure coefficient on the outer surface of the building, but the actual wind pressure measurement of high-rise buildings is difficult to carry out. In order to obtain the effective wind pressure coefficient of the building and the application of the extended lattice Boltzmann method (LBM) in the wind resistance of high-rise buildings, in this paper, the wall-adapting local eddy (WALE) model, dynamic Smagorinsky model (DSM), and Smagorinsky model (SM) are embedded into LBM with multiple-relaxation-time (MRT) format. Three LBM large eddy simulation models, MRT-LBM-WALE, MRT-LBM-DSM, and MRT-LBM-SM, which can simulate the flow around a bluff body with high Rayleigh number, are constructed by using the subgrid eddy viscosity to modify the kinematic viscosity of LBM. Finally, the three turbulence models are used to simulate and analyze the three-dimensional steady wind flow field of a single high-rise building of the standard CAARC high-rise building model in the atmospheric boundary layer, and the numerical results are analyzed and compared with the wind tunnel test results. The results show that the numerical simulation better reflects the flow characteristics and surface wind pressure of the wind environment around the high-rise building. On the windward side, it fits well with the test results. On the crosswind side and leeward side, the numerical simulation results are between the NPL and TJ-2 test results. The windward side is subject to positive pressure, which is the highest at 2/3 of the height of the windward side and low on both sides and below. The leeward and crosswind surfaces of the building are all under negative pressure. The simulation results of the three turbulence models have little difference, which provides a basis for the study of the flow around the bluff body of high-rise buildings. It is proved that the numerical solutions of the three models are in good agreement with the experimental solutions, and the real subgrid eddy viscosity near the wall can be obtained, which can accurately predict the development of turbulent flow.